Spiking Signatures of Spontaneous Activity Bursts in Hippocampal Cultures - Pimashkin, Alexey; Kastalskiy, Innokentiy; Simonov, Alexander; Koryagina, Ekaterina; Mukhina, Irina; Kazantsev, Victor (Frontiers in Computational Neuroscience, 2011)
Dense dissociated hippocampal cultures are known to generate spontaneous bursting electrical activity which can be recorded by multielectrode arrays (MEA). We have analyzed spatio-temporal profiles of spike distribution in the bursts recorded after two weeks in vitro. We have found statistically significant similarity between the spiking patterns in the consequent bursting events treated here as spiking signatures. The signatures may appear in different parts of the bursts including the activation patterns – the first spike times in the bursts, and deactivation patterns – the last spike times in the bursts. Moreover, these patterns may display apparent time scaling, e.g. they may be replayed in the subsequent bursts at different speeds preserving the spiking order. We discuss how such properties of the bursts may be associated with the formation of repeatable signalling pathways in cultured networks in vitro